MODERN APPROACHES TO IMPROVING THE QUALIFICATION OF MANAGERS, TEACHERS AND SPECIALISTS OF PRESCHOOL AND SCHOOL EDUCATION - INOYATOV, Ulugbek Ilyasovich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article describes modern mechanisms for diversifying educational services in advanced training and profes- sional retraining courses for managers, teachers and specialists of preschool and school educational institutions. These measures include mastering modern theories of learning, forming a holistic educational system, developing competencies in the field of a personality-oriented approach, updating formats, content and methods of teaching, as well as changing approaches to assessing the quality of personnel training.